2020
DOI: 10.1177/1055665619900624
|View full text |Cite
|
Sign up to set email alerts
|

Airway Morphological Changes in Pierre Robin Sequence: A Retrospective Study

Abstract: Objective: To investigate airway morphology changes in patients with Pierre Robin sequence (PRS) pre–/post–mandibular distraction osteogenesis (MDO) and to compare morphologic changes to age-matched controls. Design: Retrospective case–control study. Setting: Urban, academic, tertiary medical center. Patients, Participants: Fifteen patients with PRS after MDO to relieve upper airway obstruction (UAO) (2008-2018); age-matched controls for post-MDO patients. Interventions: Mandibular distraction osteogenesis, cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(31 citation statements)
references
References 20 publications
(19 reference statements)
1
29
1
Order By: Relevance
“…Expansion in particular segments of the upper airway including the retropalatal and retroglossal regions have been shown to correlate with physiologic response to airway expansion and the overall morphologic changes of the airway may provide a more predictive model than airway volume alone. 17 We have found that a small percentage of our patients, in particular those with an associated syndrome, have a recurrence in obstruction some time post-distraction. The airway volume growth charts may provide a clinical instrument to delineate how the airway of these patients has changed over time both relative to their own prior dimensions as well as compared to the general population.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…Expansion in particular segments of the upper airway including the retropalatal and retroglossal regions have been shown to correlate with physiologic response to airway expansion and the overall morphologic changes of the airway may provide a more predictive model than airway volume alone. 17 We have found that a small percentage of our patients, in particular those with an associated syndrome, have a recurrence in obstruction some time post-distraction. The airway volume growth charts may provide a clinical instrument to delineate how the airway of these patients has changed over time both relative to their own prior dimensions as well as compared to the general population.…”
Section: Discussionmentioning
confidence: 56%
“…Expansion in particular segments of the upper airway including the retropalatal and retroglossal regions have been shown to correlate with physiologic response to airway expansion and the overall morphologic changes of the airway may provide a more predictive model than airway volume alone. 17…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous work showed that the increase in airway size preferentially affects the retropalatal space, which can lead to supraphysiologic airway dimensions. 18 Over 90% of patients in that study had a CP, suggesting that morphologic changes in the cleft affected by MDO contributed to the observed changes in airway size. This is supported by Murage et al 19 who found that the absence of a CP was associated with failure of distraction.…”
Section: Discussionmentioning
confidence: 75%
“…17 However, these static predictions do not provide a physiologic measurement of the frequency and severity of OSA and do not correlate with physiologic improvements on post-distraction PSG. 22…”
Section: Discussionmentioning
confidence: 99%